AB0538 Assessment of Neurological Manifestations in Temporal Arteritis. (15th July 2016) - Aranda-Valera, C.; García, S.; Monjo, I.; Rodríguez, M.J.; Martín-Mola, E.; De Miguel, E.
Abstract : Background: Temporal Arteritis (TA) is a vasculitis characterized by systemic and ischemic symptoms that concern fundamentally supraaortic blood vessels. The neurological clinic can be expressed as: headache, visual alterations, affection of cranial nerves, transient ischemic attack (TIA) or ischemic stroke in carotid or vertebrobasilar territory. The ocular affection is the most frequent but other neurological ischemic affections, not retinals, are not rare but they often occur unnoticed and are attributed to atherosclerosis given the age of the patients. Being a treatable and preventable process, there is an opportunity to improve the diagnosis of this affection. Objectives: Assess the vascular events of supraaortic blood vessels, ocular vessels and non ocular vessels in our vasculitis surgery. Methods: A retrospective study was carried out on the clinical history of the patients sent to our vasculitis surgery on suspicion of TA. The diagnosis of arteritis or nonarteritic neurological affection was realized in agreement with usual clinical criteria. The variables registered were age and sex, cardiovascular risk factors (CVR), clinical manifestations, VSG and PCR values, the final diagnosis and the results of the biopsy and the ultrasound examination, as well as the number of affected branches, brain TAC and MRI. The statistical analysis was realized by means of the software program SPSS Statistics version 20.0. Results: Of the 163 patients studied, 112 were women and 51 men (31, 3% vs 68, 7%). One hundred thirteen patients (59, 32%) had definite diagnosis of TA while 50 (30, 68%) presented other diagnoses. Of the total of the patients, 59 (24 men and 35 women) presented neurological clinic: diplopía 10, loss of vision 48, TIA 7 and ACVA 4. Of these 42 were diagnosed with arteritic neurological affections (secondary to TA): 6 diplopía, 35 loss of vision, 4 TIA and 2 ACVA. Among the patients with nonarteritic and arteritic neurological events no differences were found for sex, VSG, PCR, blurry vision, fever, loss of vision, diplopía, TIA, ACVA, CVR, smoking and atrial fibrillation (AF): there was only significant differences for age. The analysis of the patients diagnosed with TA, withand without neurological events, appear in the table. Conclusions: Non ocular central neuroischemic events are frequent and affect 10, 62% of the patients with TA. Among the patients with TA the neuroischemic risk associates to being a male, advanced age, a greater number of affected branches in ultrasound examination and to the presence of headache. Disclosure of Interest: None declared